2003
DOI: 10.1002/ajpa.10306
|View full text |Cite
|
Sign up to set email alerts
|

Secular change in body height and cephalic index of Croatian medical students (University of Rijeka)

Abstract: An investigation of body height and cephalic measurements was performed among five groups of first-year medical students of the University of Rijeka School of Medicine (Rijeka, Croatia). Body height and different cephalic measurements showed normal distribution, both in male and female students. Differences between measured variables were statistically analyzed by ANOVA. No significant difference with regard to year of birth was found in either males or females. The cephalic index showed no statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
(8 reference statements)
0
19
0
2
Order By: Relevance
“…Investigations carried out on secular change in body height and cephalic index of Croatian medical students revealed a significant increase of dolichocephalic and mesocephalic and a significant decrease of brachycephalic head shape in both sexes suggesting a continuity of the debrachycephalization process (Buretic´-Tomljanovic´ et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Investigations carried out on secular change in body height and cephalic index of Croatian medical students revealed a significant increase of dolichocephalic and mesocephalic and a significant decrease of brachycephalic head shape in both sexes suggesting a continuity of the debrachycephalization process (Buretic´-Tomljanovic´ et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Bagga [34], also reported that tendency increasing height either absent or less evident in rural and tribal communities and populations from the less developed countries. It has been established in many previous researches that adult height depends on genetic and environmental factors, and on the interaction between them [35]. Silventoinen [36], provided an excellent review of the factors affecting adult height and mentioned that in modern Western societies, about 20% of variation in body height is due to environmental variation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the principal component analysis reveals that the first principal component, highly correlated with standing and shoulder heights (element of eigenvector = 0.86 and 0.74, respectively, in females, and 0.82 and 0.72 in males), has a somewhat higher correlation with head length (0.33 in females and 0.43 in males) than with head width (−0.10 in females and −0.01 in males). Furthermore, Buretic-Tomljanovic's (2004) illustrations also suggest that head length increased in parallel with body height from 1939 to 1983 in Croatian males.…”
Section: Cranial Length Changes In Parallel With Stature?mentioning
confidence: 89%
“…Further, Buretic-Tomljanovic's (2004) illustrations suggest that, as body height increased, cephalic index and head breadth tended to decrease from 1939 to 1983 in Croatian males. This means an inverse correlation between cranial Figure 5.…”
Section: Ecological Correlations Of Basi-bregamatic Height With Postcmentioning
confidence: 95%